Health and Academic Performance With Happy Children: A Controlled Longitudinal Study Based on the HOPP Project - Nandu Goswami; Nandu Goswami; Nandu Goswami; Dominique Hansen; Goran Gumze; Bianca Brix; Karin Schmid-Zalaudek; Per Morten Fredriksen; Per Morten Fredriksen (Frontiers in Cardiovascular Medicine, 2022)
BackgroundOverweight/obesity in children and adolescents, largely arising due to increased food intake and reduced physical activity, is a major health concern. Physical activity (PA) integrated into learning has been shown to not only lead to improved health outcomes and wellbeing but also positively affect academic performance. The Health and Academic Performance with Happy Children (HAPHC) project aims at enhancing health and academic performance in elementary school children via implementation of a daily unit of Physical Activity Across the Curriculum (PAAC), which is carried out within the school setting. In this project, PA as an integrated part of learning will be evaluated and the learning material adapted for a large scale implementation across several European countries.MethodsIn three European countries (Austria, Slovenia, and Belgium), 12 primary schools in total will be recruited to act as either intervention or control school in a large intervention study, which applies the PAAC pedagogy during lectures. It is estimated that, at least 3,000+ children across the three countries will be recruited in this study. All teachers of intervention schools will receive training and materials/teaching equipment that will allow them to integrate a daily PA unit of 45 min over 3 years across the curriculum. In response to the daily PA intervention, the following primary outcomes will be assessed: changes in health related physiological factors, academic achievement, psycho-social aspects and wellbeing.Impact of ProjectThe HAPHC project aims at promoting public health by increasing PA at an early age within the school setting and therewith preventing the increasing risk of non-communicable diseases across Europe. HAPHC project aims to develop knowledge and materials, which will ensure that the PAAC can be scalable to other European countries.Trial Registration NumberClinicalTrials.gov, identifier: NCT04956003.